Analysis of urinary potassium isotopes and association with pancreatic health: healthy, diabetic and cancerous states - Schilling, Kathrin; Chen, Heng; Glabonjat, Ronald A.; Debernardi, Silvana; Blyuss, Oleg; Navas-Acien, Ana; Halliday, Alex N.; Crnogorac-Jurcevic, Tatjana (Frontiers in Endocrinology, 2024)
More than 700 million people worldwide suffer from diseases of the pancreas, such as diabetes, pancreatitis and pancreatic cancer. Often dysregulation of potassium (K + ) channels, co-transporters and pumps can promote development and progression of many types of diseases. The role of K + transport system in pancreatic cell homeostasis and disease development remains largely unexplored. Potassium isotope analysis (d 41 K), however, might have the potential to detect minute changes in metabolic processes relevant for pancreatic diseases. We assessed urinary K isotope composition in a case-control study by measuring K concentrations and d 41 K in spot urines collected from patients diagnosed with pancreatic cancer (n=18), other pancreas-related diseases (n=14) and compared those data to healthy controls (n=16). Our results show that urinary K levels for patients with diseased pancreas (benign and pancreatic cancer) are significantly lower than the healthy controls. For d 41 K, the values tend to be higher for individuals with diseased pancreas than for healthy individuals but the difference is not significant (p=0.08). For diabetics, urinary K levels are significantly lower and d 41 K is significantly higher than for the healthy controls. These results suggest that urinary K levels and K isotopes can help identify K disturbances related to diabetes, an associated factors of all-cause mortality for diabetics. Although the K isotope results should be considered exploratory and hypothesis-generating and future studies should focus on larger sample size and d 41 K analysis of other K-disrupting diseases (e.g., chronic kidney disease), our data hold great promise for K isotopes as disease marker.